Ectopic Expression of PtoMYB74 in Poplar and Arabidopsis Promotes Secondary Cell Wall Formation - Li, Chaofeng; Ma, Xiaodong; Yu, Hong; Fu, Yongyao; Luo, Keming (Frontiers in Plant Science, 2018)
In higher plants, R2R3-MYB transcription factors are important regulators of secondary cell wall formation. Although 192 annotated R2R3 MYB genes were identified in poplar genome, only a few members were characterized to participate in the regulation of secondary cell wall biosynthesis. In this paper, we identify a R2R3-MYB transcription factor, PtoMYB74, which is predicted to be an orthologue of Arabidopsis AtMYB61, a transcription activator that regulates secondary cell wall formation, lignin biosynthesis, stomatal aperture and the mucilage of seed coat. PtoMYB74 is mainly expressed in stems, especially in the xylem tissues and organs. PtoMYB74 as a transcriptional activator is localized to the nucleus. The overexpression of PtoMYB74 increased the secondary cell wall thickness of vessels in transgenic poplar and changed secondary cell wall compositions. The expression levels of lignin and cellulose biosynthetic genes were elevated in transgenic poplar overexpressing PtoMYB74 compared to the wild type, while xylan biosynthetic genes were not changed. Transcriptional activation assays demonstrated that PtoMYB74 could activate the promoters of structural genes in lignin and cellulose biosynthetic pathways. Taken together, our data show that PtoMYB74 positively regulates secondary cell wall biosynthesis in poplar.